University Selection Determinants in Vietnam: A Case Study of Thai Nguyen University of Information Technology and Communication - Bùi Ngoc Tuan (CV FOUNDAE, 2024)
This study examines the factors influencing students' decisions to choose the Thai Nguyen University of Information and Communication Technology (ICTU). The research helps universities understand the key factors that students consider, leading to more effective admission policies and strategies. Data was collected from a random sample of first-year students at the university in 2022 using questionnaires and both qualitative and quantitative methods with SPSS 20 software. The integration of these two methods was carried out through the Structural Equation Modeling (SEM), allowing a comprehensive analysis and evaluation of the influencing factors. Factor analysis indicated that a multiple regression model was suitable for assessing the factors influencing enrollment decisions. Important variables included adequate classrooms, a well-equipped library, generous scholarships, supportive employment policies during studies, a curriculum aligned with social needs, high-earning graduates, and highly qualified faculty. The SEM model demonstrated a good fit with high compatibility and accuracy indices, supporting the model’s validity and explanatory power. The article recommends enhancing faculty quality, improving infrastructure, diversifying programs, and increasing the dissemination of university information